Ficus carica polysaccharide extraction via ultrasound-assisted technique: Structure characterization, antioxidant, hypoglycemic and immunomodulatory activities - Wang, Weilan; Liu, Xiaoying; Wang, Lixue; Song, Guirong; Jiang, Wei; Mu, Lihong; Li, Jinyao (Ultrasonics sonochemistry, 2023)
In this research, the ultrasound-assisted extraction (UAE) conditions of the water-soluble polysaccharide (FCPS) from Ficus carica fruits were optimized using the response surface methodology. The optimal FCPS yield was 7.97 % achieved by conducting ultrasound-assisted extraction four times at a solid-liquid ratio of 1:20 (g/mL) and an ultrasound temperature of 70 °C. Then, the structure, antioxidant properties, hypoglycemic effects, and immunomodulatory activities of FCPS were evaluated. FCPS was characterized as irregular, rough-surfaced, flaky materials consisting of pyran-type polysaccharides with α- and β-glycosidic linkages, and composed of multiple monosaccharides and only one homogeneous concentrated polysaccharide component (FCPS1) with a molecular weight of 4.224 × 10 Da. The results suggested FCPS exhibited remarkable antioxidant activity in vitro, as evidenced by improved cell viability and reduced the reactive oxygen species (ROS) levels. Meanwhile, FCPS effectively improved liver-related insulin resistance by promoting glucose consumption in hepatocytes and activated the immune response through activation of murine bone marrow-derived dendritic cells (DCs) and upregulation of interleukin 6 (IL6) and interleukin 12 (IL-12) expression. The findings demonstrate the efficacy of the UAE technique in isolating FCPS with biological functionality and FCPS could potentially serve as a beneficial organic antioxidant source and functional food, carrying important implications for future studies.